2011
DOI: 10.1089/ars.2010.3203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxidative Stress on Behavior, Physiology, and the Redox Thiol Proteome ofCaenorhabditis elegans

Abstract: Accumulation of reactive oxygen species has been implicated in various diseases and aging. However, the precise physiological effects of accumulating oxidants are still largely undefined. Here, we applied a short-term peroxide stress treatment to young Caenorhabditis elegans and measured behavioral, physiological, and cellular consequences. We discovered that exposure to peroxide stress causes a number of immediate changes, including loss in mobility, decreased growth rate, and decreased cellular adenosine tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
103
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(108 citation statements)
references
References 50 publications
5
103
0
Order By: Relevance
“…Superoxides are converted to hydrogen peroxide by superoxide dismutases (SOD) followed by a conversion to water by catalases (CTL) or peroxiredoxins (PRDX) (Sies, 2014). The C. elegans genome encodes 5 different superoxide dismutases ( sod‐1 to sod‐5 ), three different catalases ( ctl‐1 to ctl‐3 ), and three peroxiredoxins that are named according to their homology to the mammalian peroxiredoxins, prdx‐2 , prdx‐3, and prdx‐6 (Doonan et al ., 2008; Olahova et al ., 2008; Kumsta et al ., 2011). …”
Section: Resultsmentioning
confidence: 99%
“…Superoxides are converted to hydrogen peroxide by superoxide dismutases (SOD) followed by a conversion to water by catalases (CTL) or peroxiredoxins (PRDX) (Sies, 2014). The C. elegans genome encodes 5 different superoxide dismutases ( sod‐1 to sod‐5 ), three different catalases ( ctl‐1 to ctl‐3 ), and three peroxiredoxins that are named according to their homology to the mammalian peroxiredoxins, prdx‐2 , prdx‐3, and prdx‐6 (Doonan et al ., 2008; Olahova et al ., 2008; Kumsta et al ., 2011). …”
Section: Resultsmentioning
confidence: 99%
“…actin biogenesis 89 ) and CDC-48 (e.g., targeting of retro-translocated ERAD substrates 90 ). 91 So far, it is unknown if these oxidative-sensitive cysteines have an activating or inhibiting function. For the mammalian homolog of HSP-1, Hsc70, it could be shown that oxidation of an internal thiol through glutathione accelerated the Hsc70 activity in protein aggregate prevention in vitro.…”
Section: Redox-regulation Of Chaperonesmentioning
confidence: 99%
“…95 C. elegans has also been used as a model for redox proteomic analysis and fluorescent biosensors. 15,91,96,97 Redox sensors…”
Section: Redox-regulation Of Chaperonesmentioning
confidence: 99%
See 2 more Smart Citations